Toward QbD Process Understanding on DNA Vaccine Purification Using Design of Experiment - Hocharoen, Lalintip; Noppiboon, Sarawuth; Kitsubun, Panit (Frontiers in Bioengineering and Biotechnology, 2021)
DNA vaccines, the third generation of vaccines, become of interest and is one of promising therapy for many diseases as they offer the customization of their ability on protection and treatment with high stability. The production of DNA vaccines is considered rapid and less complicated comparing to others such as mRNA vaccine, viral vaccine or subunit protein vaccine. However, the most critical concern for DNA vaccine is on how to produce the active DNA, a supercoiled isoform, to comply with the regulations. Our work therefore focuses on gaining a process understanding of the purification step which process parameters that have impacts on the critical quality attribute (CQA), %supercoiled DNA and performance attribute (PA), %Step yield. Herein, pVax1/lacZ was used as a model. The process parameters of interest were sample application flow rates, salt concentration at washing step and at elution step in the hydrophobic interaction chromatography (HIC). Using Design of Experiment (DoE) with central composite face centered (CCF) approach, 14 experiments plus four additional runs at the center points were created. The response data was used to establish regression predictive models and simulation was conducted in 10,000 runs to provide tolerance interval of these CQA and PA. The approach of this process understanding can be applied for Quality by Design (QbD) on other DNA vaccines and in larger production scale as well.